Modeling and Simulation of Linear Triblock Copolymers under Three-Dimensional Confinement (CSIAM Transactions on Applied Mathematics, 2023)
We studied linear triblock copolymer and homopolymer mixtures and constructed a new Nakazawa-Ohta-type model to describe the phase separation of thesystem. For this high-order, nonlocal and multicomponent phase field system, we construct two second-order, linear and energy-stable schemes. We also proved the energydissipation and mass conservation of the schemes. Finally, numerical simulations werepresented in the 3D case, which verified the theoretical analysis. In addition to thosereported phase structures, we found some new ones, which can give some guidanceto experimenters.